Practical guidebook on data disaggregation for the sustainable development goals (Manila,Philippines Asian Development Bank, 2021)
The leave no one behind principle espoused by the 2030 Agenda requires measures of progress for different segments of the population. This entails detailed disaggregated data to identify subgroups that might be falling behind, to ensure progress toward achieving the Sustainable Development Goals (SDGs). ADB and the Statistics Division of the United Nations Department of Economic and Social Affairs developed this practical guidebook with tools to collect, compile, analyze, and disseminate disaggregated data. It also provides materials on issues and experiences of countries regarding data disaggregation for the SDGs.
Keywords: Sustainable development; Economics; Electronic books